Mathematics anxiety among secondary school students in aizawl and shillong: A comparative study - Lalsangpuii, C.; Zohmingliani, Lynda (SCHOOL SCIENCE, 2025)
The present study was conducted to compare the mathematics anxiety of secondary school students in Aizawl and Shillong. Descriptive survey method was employed in which Stratified Random Sampling has been adopted to collect a sample of 364 secondary school students. The tool used for collecting data was Mathematics Anxiety Scale developed by the investigator. It was found that there was no significant difference in the mathematics anxiety of secondary school students in Aizawl and Shillong. Furthermore, it was also found that there was no significant difference in the mathematics anxiety between male secondary school students of Aizawl and Shillong, as well as female students of the two cities.